419 Endovascular Aortic Repair of Abdominal Aortic Aneurysm Early Re-Intervention Outcome, A District General Hospital Experience. (4th May 2021) - Soliman, H; Girish, G; Shahed, S
Abstract: Introduction: Endovascular repair (EVAR) transformed abdominal aortic aneurysm (AAA) management. However, it is associated with higher re-intervention rate compared with open repair. This audit evaluates the early re-intervention rate at Watford General Hospital relative to the 4-yearly average rate in the draft evidence review by NICE (16.89%). Method: EVAR procedures performed in 2015 and 2016 were retrieved. The follow up was analysed to identify re-intervention procedures performed to address complications related to the initial EVAR or sac expansion. Results: 108 patients underwent EVAR during the 2-year inclusion period. 21 re-interventions (19.4%) were recorded, irrespective of type or cause of re-intervention. 30 patients (28.6%) developed endoleak but only 17 (56.7%) had a re-intervention. Type 1 endoleak was the main cause for re-intervention (28.6%). The majority of re-interventions were executed endovascularly (57%). 47.6% of the re-interventions were done during the first year following EVAR. Conclusions: Even though our re-intervention rate was relatively above the international average, EVAR is still considered safe for AAA repair with low morbidity and mortality. As re-interventions are frequently required, long-term surveillance is essential. Conversely, most of re-interventions can be performed with minimal morbidity. We recommend discussing all cases in a formal MDT before surgery and any re-intervention.